Motivating factors for consumers to participate in takāful: a survey by Indian insurance policyholders - Salman, Syed Ahmed; Hassan, Rusni (Emerald Group Holdings Ltd., 2020)
Purpose – The purpose of this study is to examine the perception and acceptability of insurance policyholders to introduce takaful in India. The primary focus of this research is insurance policyholders because they currently have insurance policies and it is believed that they are familiar with the concept of insurance, compared to the people who do not have any insurance policy. Design/methodology/approach – New product diffusion theory is used in developing the hypothesis and a questionnaire. In this research, the population is unknown, and hence, the non-probability sample is used. Quota sampling and snowball sampling methods are used in this survey, with a sample size of 909 respondents, including Muslim and non-Muslim policyholders. The external factors that motivate potential policyholders to participate in takaful are the independent variable here; while the respondents’ actual willingness to participate in takaful is the dependent variable. Regression analysis is performed to analyse the data. Findings – Based on 909 respondents, it is found that the factors such as cost vs benefits, marketing and promotion and social and religion play a significant role in a consumers’ decision-making at 1% significant level overall. The attribute of agents can influence the consumers at a 10% significant level overall. However, other factors, namely, accessibility, availability and service quality, product features and reputation of the company cannot pursue the consumers in India. Research limitations/implications – The questionnaires are distributed in 10 cities from nine states out of 28 states in India. Thus, it covers only one-third of the states. Future research can expand the respondents from other states that have not been researched. Practical implications – India is opening to foreign investments in the Indian insurance industry, and thus, the findings are useful for industrial players, investors, policymakers for the development of takaful in India. Originality/value – Limited research has been done in previous studies and this research is the pinnacle within-depth survey regarding takaful in India